The impact of foreign aid on growth and savings in developing countries - Durbarry, Ramesh (1998)
Developing countries have received foreign aid and other forms of capital flows for a long time, although they have been subject to some fluctuations. The key question is whether these flows have helped them in achieving their objectives? Aid has been evaluated at two levels: micro and macro. While micro evaluations have found that in most cases aid 'works' (for example Cassen et al., 1986), those at the macro-level are ambiguous. This thesis is predominantly concerned with the macroeconomic impact of foreign aid. There have been considerable efforts to improve both the theoretical and empirical literature on aid effectiveness, both suffer from serious weaknesses and shortcomings. At the theoretical level, there are not many models which capture the full potential of foreign aid within a consistent, fully specified, growth framework, while existing empirical studies are flawed by model mispecification, questionable sample composition and size, and inappropriate econometric techniques. This has led to inconclusive and often misleading results in assessing the effectiveness of foreign aid.